Making Furniture in Preindustrial America : The Social Economy of Newtown and Woodbury, Connecticut - Cooke, Edward S.; Project Muse. (Baltimore, Md. : Johns Hopkins University Press, 2019)
In Making Furniture in Preindustrial America Edward S. Cooke Jr. offers a fresh and appealing cross-disciplinary study of the furnituremakers, social structure, household possessions, and surviving pieces of furniture of two neighboring New England communities. Drawing on both documentary and artifactual sources, Cooke explores the interplay among producer, process, and style in demonstrating why and how the social economies of these two seemingly similar towns differed significantly during the late colonial and early national periods. Throughout the latter half of the eighteenth century, Cooke explains, the yeoman town of Newtown relied on native joiners whose work satisfied the expectations of their fellow townspeople. These traditionalists combined craftwork with farming and made relatively plain, conservative furniture. By contrast, the typical joiner in the neighboring gentry town of Woodbury was the immigrant innovator. Born and raised elsewhere in Connecticut and serving a diverse clientele, these craftsmen were free of the cultural constraints that affected their Newtown contemporaries. Relying almost entirely on furnituremaking for their livelihood, they were free to pay greater attention to stylistically sensitive features than to mere function.
List of Tables and Charts -- Acknowledgments -- Introduction: The Need for the Artisanal Voice (starting p. 3) -- 1 The Preindustrial Joiner in Western Connecticut, 1760-1820 (starting p. 13) -- 2 The Social Economy of the Preindustrial Joiner (starting p. 33) -- 3 The Joiners of Newtown and Woodbury (starting p. 49) -- 4 Socioeconomic Structure in Newtown and Woodbury (starting p. 69) -- 5 Consumer Behavior in Newtown and Woodbury (starting p. 91) -- 6 Workmanship of Habit: The Furniture of Newtown (starting p. 118) -- 7 Workmanship of Competition: The Furniture of Woodbury (starting p. 151) -- Conclusion: The Response to Market Capitalism (starting p. 190) -- Appendix A: Biographies of Newtown Joiners, 1760-1820 (starting p. 201) -- Appendix B: Biographies of Woodbury Joiners, 1760-1820 (starting p. 217) -- Notes (starting p. 233) -- Glossary of Furniture Terms (starting p. 273) -- Note on Sources and Methods (starting p. 277) -- Index (starting p. 285)
Originally published as Johns Hopkins Press in 1996.
The text of this book is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License.
Open access edition supported by the National Endowment for the Humanities / Andrew W. Mellon Foundation Humanities Open Book Program.
Description based on print version record.
Keywords: Möbeltischlerei; Economic history; Furniture; Furniture industry and trade; Meubles -- Connecticut -- Newtown -- Histoire -- 18e siecle; Meubles -- Connecticut -- Newtown -- Histoire -- 19e siecle; Meubles -- Connecticut -- Woodbury -- Histoire -- 18e siecle; Meubles -- Connecticut -- Woodbury -- Histoire -- 19e siecle; Meubles -- Industrie -- Connecticut -- Histoire; Furniture -- Connecticut -- Newtown -- History -- 18th century; Furniture -- Connecticut -- Newtown -- History -- 19th century; Furniture -- Connecticut -- Woodbury -- History -- 18th century; Furniture -- Connecticut -- Woodbury -- History -- 19th century; Furniture industry and trade -- Connecticut -- History; Neuengland; Connecticut; Connecticut -- Newtown; Connecticut -- Woodbury; Newtown (Conn.) -- Economic conditions; Woodbury (Conn.) -- Economic conditions; History; Electronic books